PENGARUH PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR AKADEMIK TERHADAP KINERJA GURU DI SMK PGRI TANJUNG RAJA - Sepriadi, Sepriadi; Ahmad, Syarwani (Graduate Program Magister Manajemen Pendidikan, 2017)
This study aimed at determining (1) leadership of headmasterâs Vocational School of PGRI Tanjung Raja as academic supervisor; (2) the teachersâ performance of Vocational School of PGRI Tanjung Raja; and (3) the influence of headmasters leadership on the teachersâ performance of Vocational School of PGRI Tanjung Raja. This research was quantitative research with expostfacto approach. The population in this study were the teachers of Vocational School PGRI Tanjung Raja consist of 85 teachers and then the sample was 60 teachers which selected by area proportional random sampling technique. The data collection instrument was questionnaire with Likert scale which has 4 alternative answers, on 100 items. The data analysis was used simple regression analysis technique. The results showed (1) leadership of headmasterâs Vocational School of PGRI Tanjung Raja according to some teachers (52%) high category; then (2) the teachersâ performance of Vocational School PGRI Tanjung Raja (52%) high category; and (3) there is a positive and significant influence of headmaster leadership as academic supervisor on teachersâ performance 65,1% happened to teacherâs performance can be explained by headmaster leadership as academic supervisor, while 80,7% other explained by other variable not included in this study such as teacherâs knowledge, teachersâ personality, dedication, professional development, and so forth.Kata Kunci: Headmasterâs Leadership, Teachersâ Performance, Vocational School PGRI Tanjung Raja